CFD analysis of a multiplatform catamaran by means of a web-based application: Experimental data comparison for a fully automated analysis process. (November 2021) - Salvadore, Francesco; Ponzini, Raffaele; Duque, Javier Hernández; Reinaldos, Cristian Alcántara; Soler, Jordi Mas
Abstract: The recently introduced LincoSim Web Based High Performance Computing (HPC) Cloud Platform for Automatic Virtual Towing Tank Analysis, which is based on open-source Reynolds Averaged Navier-Stokes (RANS) solvers (Salvadore & Ponzini, 2019), is herein applied to the hydrodynamic assessment of a catamaran vessel. An experimental data campaign was used to assess the effect of the demihull separation distance on the catamaran's resistance for a given demihull shape. The results of the comparison between the experimental and the automatically generated numerical ones are presented and discussed in the present work. The comparison is quite rich including data for a reference monohull, three demihull separations and two displacements conditions, each with the Froude number ranging from 0.145 to 0.904. The set of the experimental data acquired for the model scaled catamaran are the total resistance, the sinkage and the dynamic trim. Nevertheless, also the wave fields at three given locations are considered in the towing tank experiments in order to assess not only the effect on the hull, but also on the catamaran's wake field. The agreement between computational and experimental quantities is good for both the hull-related and flow-related ones, confirming the ability of the developed automated tool to discern between favorable and detrimental fluid dynamic conditions and to efficiently rank performances also for multihulls. Notably, thanks to the availability of numerical data for both model and full scale, also the effectiveness of the extrapolation process has been assessed.